Naval operations analysis - Wagner, Daniel H. 1925-; Mylander, W. Charles; Sanders, Thomas J. (Naval Institute Press, 1999)
This textbook for Naval Academy midshipmen focuses on search and detection theory as it was developed in World War II and evolved after the war. Accessible to anyone with a mathematical background, it covers analytical decision-making, simulation techniques, and models used in determining the probability of detection. This third edition is a comprehensive update that collects in one place the basic analytical developments in naval search theory over the last fifty years, while retaining the material on the models of search theory developed in the campaigns against the submarine threat in World War II. With recent improvements in stealth technology, the need to become more knowledgeable about search theory is increasing.